(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) has been understood as a developmental disorder that affects the basic brain mechanisms of sociability and communication at an early stage, generating uncertainty regarding its understanding, especially among parents and family members. Given the growing number of students with ASD, this study sought to understand the main difficulties faced by families of children on the autism spectrum enrolled in Municipal Early Childhood Education Centers (CMEIs), in order to provide practical guidance under the perspective of physiotherapy through an e-book to assist them in effective treatment strategies. The research instruments developed were based on the CARS2 – QPC questionnaire, specific for parents or caregivers of children with ASD. The questionnaires included objective questions in order to cover a wide range of relevant areas, including diagnosis and understanding of ASD, access to health services, emotional and financial impact, coping strategies, difficulties and limitations faced. The results indicate that the greatest difficulties faced by families are related to reconciling the demands of caring for an autistic child with other family or professional responsibilities and the difficulty of adapting children to new situations, environments or changes in routine. It is observed that most parents have a satisfactory understanding of the spectrum. However, families still face numerous challenges, highlighting the importance of constantly learning about autism so that they can provide the best support for their children.